2018
DOI: 10.1039/c7nr07283j
|View full text |Cite
|
Sign up to set email alerts
|

Generating plasmonic heterostructures by cation exchange and redox reactions of covellite CuS nanocrystals with Au3+ ions

Abstract: We demonstrate the fabrication of various types of heterostructures, including core-shells and dimers. This is achieved by reacting platelet-shaped covellite (CuS) nanocrystals (NCs) with Au ions under various reaction conditions: the exposure of CuS NCs to Au ions, in the presence or in the absence of ascorbic acid (AA), leads to the formation of CuS@Au core-shell nanostructures; the reaction of CuS NCs with Au ions in the presence of oleylamine (OM) leads to the formation of CuS@AuS; the presence of both OM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 50 publications
1
36
0
Order By: Relevance
“…When the metastable Cu 2−x S@Au 2 S core–shell NPs were irradiated with an electron beam, the NPs were converted into a dumbbell-like shape because the electron beam provided energy to transform them into a stable structure. The cation exchange reaction between Cu and Au in CuS was also observed by Hu et al [94]. Through the cation exchange reaction from covellite CuS, various Au–CuS NPs with heterostructures such as CuS@Au core–shell NPs, CuS@Au 2 S core–shell NPs, and an Au/CuS dimer were synthesized by using ligands such as OA and ascorbic acid (Fig.…”
Section: Other Cation Exchange Reactionsmentioning
confidence: 54%
See 1 more Smart Citation
“…When the metastable Cu 2−x S@Au 2 S core–shell NPs were irradiated with an electron beam, the NPs were converted into a dumbbell-like shape because the electron beam provided energy to transform them into a stable structure. The cation exchange reaction between Cu and Au in CuS was also observed by Hu et al [94]. Through the cation exchange reaction from covellite CuS, various Au–CuS NPs with heterostructures such as CuS@Au core–shell NPs, CuS@Au 2 S core–shell NPs, and an Au/CuS dimer were synthesized by using ligands such as OA and ascorbic acid (Fig.…”
Section: Other Cation Exchange Reactionsmentioning
confidence: 54%
“…The synthesized CdSe nanobelts exhibited rapid, stable, and repeatable photoelectric properties when used as photodetectors.
Fig. 12An illustration of the various reaction conditions and related heterostructures of Au or Au 2 S–CuS at room temperature(Reprinted with permission from the Royal Society of Chemistry [94])
…”
Section: Other Cation Exchange Reactionsmentioning
confidence: 99%
“…46 It is reported to be a highly metastable phase, decomposing both under inert atmosphere and air conditions at temperatures above 420 K, and its preparation often leads to amorphous solids, with a few exceptions at the nanoscale. 46,[52][53][54] It is worth mentioning that the crystallinity of the Au2S nanostructures reported here is highly preserved at room temperature for months after preparation. Additionally, spherical and rod-like Au2S NPs with a hollow morphology like the ones described in this work have not been reported to date and, after appropriate functionalization and water transfer, they open up the doors for the use of such a priori biocompatible elongated nanostructures as potential nanocontainers for dual diagnostic and therapeutic applications, in line with our recent studies about biomedical applications of noble metal-based chalcogenides analogous to the ones described in this work.…”
Section: Reaction Mechanismmentioning
confidence: 76%
“…The purple emission band at 330-450 nm and the strong blue emission peak at 395 nm are attributed to surface defects of CuS nanocrystals. 23 As the reaction temperature increased from 120°C to 150°C, the luminescence intensity at 395 nm was attributed to the higher temperature, resulting in more defects of CuS nanocrystals. These defects enhanced the luminescence intensity of CuS nanocrystals, which indicated that the surface defect concentration of CuS nanocrystals is affected by the reaction temperature ( Figure 3A…”
Section: Structure and Morphologymentioning
confidence: 99%